The Causes and Consequences of Rural-urban Migration: The Case of Wolaita Sodo Town Merhal Sub-City. - Mesele Woldemichael Delango (Budapest International Research and Critics University, 2019)
In developing countries like Ethiopia rural-urban migration is an image that distresses development in both urban and rural areas. Hence, this study was aimed to identify and investigate the major causes and consequences of rural-urban migration in Wolaita Sodo town Merhal Sub-city. With a confidence level of 90%, the sample sizes of 95 target respondents were determined by using Cochran s formula for sample size determination, but due to time and budget constraints the researcher reduced the sample size in to 50 from two k respective kebeles. Both qualitative and quantitative data was collected from primary and secondary sources. The qualitative data was analyzed by using table, percentage, mean, frequency and graph and qualitative data obtained from Focus FGDs and key informants were analyzed through narration and qualitative descriptions. Hence problems such as financial (24%), unemployment (30%), inability to obtain social services (14%) and, do not get job as expected (30%) are now evident in the study areas. Taking into account the population growth of the town, constructing additional house and social service centers, such as schools, health institutions, recreational centers are important in providing needed services and better quality of life. Therefore, it needs GOs and NGOs considerable attention and other policy-makers to reflect on the most suitable ways to the existing problem.